Tantalum boride / MXenes bimetallic boride heterojunction material and preparation method and application thereof
Through step-by-step calcination reaction and vacuum melt diffusion reaction, tantalum titanium boride/MXenes bimetallic boride heterojunction material was prepared, which solved the complex preparation process of bimetallic boride heterojunction and the inability to store energy in the prior art. The problem of complete release achieves high conductivity and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411251651.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-08
AI Technical Summary
The existing bimetallic boride heterojunction preparation process is complex, the demand temperature is high, and the agglomeration is serious, resulting in poor conductivity and inability to completely release energy storage effects in lithium-sulfur batteries.
The tantalum titanium boride/MXenes bimetallic boride heterojunction material was prepared by step-by-step calcination reaction method. The tantalum boride titanium boride/MXenes bimetallic boride heterojunction material was generated by melt heating reaction under an argon atmosphere, and Combining with elemental sulfur through vacuum melt diffusion reaction, sulfur/tantalum boride titanium/MXenes bimetallic boride heterojunction material is formed.
Effectively fix elemental sulfur, inhibit the production of lithium polysulfide intermediate products, avoid shuttle effects, improve the conductivity and catalytic performance of electrode materials, and enhance the electrochemical performance of lithium sulfur batteries.
Smart Images

Figure CN119390082A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials, and in particular relates to a tantalum-titanium boride / MXenes bimetallic boride heterojunction material and a preparation method and application thereof. Background Art
[0002] Since the early 1960s, lithium-sulfur batteries have attracted extensive attention from researchers due to their high theoretical energy density, cheap and abundant raw materials, and environmental friendliness. However, the current problems of lithium-sulfur batteries, such as the poor conductivity of sulfur and lithium sulfide, the obvious volume expansion during the cycle charge and discharge, and the shuttle effect of lithium polysulfide, have not been effectively solved, which seriously restricts their commercial application.
[0003] In response to these problems, in recent years, a large number of studies have focused on solving the "shuttle effect" of lithium polysulfide. Among them, bimetallic borides can effectively slow down the oxidation of metals and increase active sites due to their unique composite catalytic activity, amphiphilic sulfur properties, and large electronegativity (X=2.04). The modified electronic structure between transition metals and boron can also reduce the kinetic energy barrier in the electrochemical process, so it can exhibit excellent electrocatalytic performance; at the same time, bimetallic borides can regulate the catalytic activity of metals, thereby improving the electrocatalytic performance.
[0004] However, since most bimetallic borides are difficult to prepare and have high synthesis temperatures, the products contain a large number of monometallic boride impurities and are severely agglomerated, they cannot fully contact with sulfur, making it impossible to exert the synergistic effect between the metal catalysts in the bimetallic borides and thus fail to fully release their energy storage activity. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art in the preparation of bimetallic boride heterojunctions, such as complex process, high temperature requirement, severe agglomeration, poor conductivity and inability to fully release the energy storage effect when used in lithium-sulfur batteries, the primary purpose of the present invention is to provide a method for preparing a tantalum titanium boride / MXenes bimetallic boride heterojunction material, which obtains a material that can effectively fix elemental sulfur and inhibit the production of soluble lithium polysulfide intermediates through a simple step-by-step calcination reaction method, thereby avoiding severe shuttle effects.
[0006] Another object of the present invention is to provide a tantalum titanium boride prepared by the above preparation method.
[0007] / MXenes bimetallic boride heterojunction material; this material can also effectively buffer the volume change of the positive electrode material and improve the conductivity of the electrode material.
[0008] Another object of the present invention is to provide an application of the above-mentioned tantalum titanium boride / MXenes bimetallic boride heterojunction material in a lithium-sulfur battery.
[0009] The purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a tantalum-titanium boride / MXenes bimetallic boride heterojunction material comprises the following steps:
[0011] S1. Weigh commercial boron powder, tantalum pentoxide, titanium dioxide, MXenes, sodium chloride and potassium chloride, mix and grind for 30 minutes to obtain a uniform precursor;
[0012] S2, placing the precursor obtained in step S1 into a porcelain boat, transferring it to a tube furnace, introducing argon gas, heating the temperature to 350-450°C at a rate of 5°C under an argon atmosphere, maintaining it for 1 hour, and then heating it again to 950-1050°C at a rate of 10°C per minute, maintaining it for 2 hours, performing a melting heating reaction, and allowing it to cool naturally to obtain a product after the reaction;
[0013] S3, adding deionized water to the product obtained in step S2, standing for 24 hours, then ultrasonically treating for 0.5 hours, and drying the obtained product at 60°C;
[0014] S4. Add deionized water to the product dried after ultrasonic treatment in step S3 again for washing, suction filtration, and freeze-drying to finally obtain a tantalum titanium boride / MXenes bimetallic boride heterojunction material.
[0015] The MXenes described in step S1 is Ti3C2.
[0016] The mass ratio of the total mass of the commercial boron powder, tantalum pentoxide and titanium dioxide described in step S1 to the total mass of sodium chloride and potassium chloride is 1:7-1:20.
[0017] The molar ratio of tantalum pentoxide, titanium dioxide and commercial boron powder described in step S1 is 1:1:3-1:1:13.
[0018] The molar ratio of MXenes to commercial boron powder described in step S1 is 1:1-1:5.
[0019] A tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared by the above-mentioned preparation method.
[0020] The application of the above-mentioned tantalum titanium boride / MXenes bimetallic boride heterojunction material in the field of lithium-sulfur batteries.
[0021] During the application process, the tantalum titanium boride / MXenes bimetallic boride heterojunction material is first mixed with elemental sulfur to obtain a mixture, and the mixture is subjected to a vacuum melt diffusion reaction to obtain sulfur / tantalum titanium boride.
[0022] / MXenes bimetallic boride heterojunction materials as positive electrode materials for lithium-sulfur batteries.
[0023] The temperature of the vacuum melting diffusion reaction is 150-160° C., and the time is 12-24 hours; the elemental sulfur accounts for 75% of the mass of the mixture.
[0024] The present invention obtains a tantalum titanium boride / MXenes bimetallic boride heterojunction material by calcining in an argon atmosphere at 950-1050°C through a step-by-step calcination method, and then prepares a sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material through a vacuum melt diffusion reaction. In the present invention, since MXenes have a high specific surface area and a large number of active sites, under high temperature conditions, they can be used as a base material for the reaction of molten boron, titanium dioxide, and tantalum pentoxide to generate tantalum titanium boride, thereby avoiding the agglomeration of the generated tantalum boride and titanium boride, and fully releasing the catalytic activity and energy storage capacity of tantalum boride. At the same time, experiments have shown that the introduction of MXenes can reduce the generation temperature of tantalum boride from more than 1300°C to 950-1050°C, optimizing the reaction temperature. The reaction principle is:
[0025] 2Ta2O5 (s) + 18B (s) → 4TaB2 (s) + 5B2O2 (g)
[0026] TiO2(s)+4B(s)→TiB2(s)+B2O2
[0027] The present invention uses a step-by-step boron reduction method, which can achieve the generation of tantalum titanium boride on MXenes at the same time, thereby synthesizing tantalum titanium boride / MXenes bimetallic boride heterojunction materials. On the one hand, the presence of MXenes can alleviate the agglomeration problem of tantalum titanium boride / MXenes bimetallic boride heterojunction materials to a certain extent, and can effectively fix elemental sulfur, so that it can fix sulfur and adsorb polysulfides through stronger chemical reactions, reduce the content of high sulfides in the electrolyte, and inhibit the shuttle effect in lithium-sulfur batteries. On the other hand, the synergistic effect between different metals can effectively regulate the surface electronic structure and catalytic efficiency of transition metal-based catalysts, further improve the catalytic conversion efficiency, and thus greatly improve the electrochemical performance of the material in lithium-sulfur batteries.
[0028] The process of the present invention is simple, low in cost, and has good controllability, safety and repeatability. It can solve the problem of agglomeration of boride heterojunctions during the preparation process and fully release their active sites, thereby solving the problem of shuttle effect caused by poor fixation of sulfur element and inhibition of polysulfide dissolution in existing lithium-sulfur battery positive electrode materials.
[0029] Compared with the prior art, the present invention has the following advantages and effects:
[0030] (1) The tantalum-titanium boride / MXenes bimetallic boride heterojunction prepared by the present invention can exert the synergistic effect of different metals, regulate the catalytic activity of the boride metal, and at the same time exert the amphiphilic sulfur effect of the boride, effectively improve the adsorption capacity of the boride for lithium polysulfide, enhance the catalytic performance, improve the conversion efficiency, and greatly inhibit the shuttle effect in the lithium-sulfur battery.
[0031] (2) The present invention uses MXenes as a conductive substrate and exerts a synergistic effect in the bimetallic synthesis process, thereby improving the agglomeration problem in the boride synthesis process, improving the boride's contact ability with sulfur, and giving full play to the catalytic activity of the boride.
[0032] (3) The present invention has low temperature, is safe and controllable, has simple steps, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared in Example 1.
[0034] Figure 2 This is the X-ray diffraction spectrum of the tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared in Example 1.
[0035] Figure 3 A rate performance diagram of the sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material provided in Example 1 of the present invention as a positive electrode of a lithium-sulfur battery;
[0036] Figure 4 This is a comparison chart of the electrochemical impedance spectroscopy (EIS) of the lithium-sulfur battery positive electrode material of the sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared in Example 1. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0038] Example 1
[0039] 1. Preparation:
[0040] S1. Weigh 0.195 g of commercial B powder, 0.364 g of Ta2O5, 0.13 g of TiO2, 2.795 g of NaCl, 2.795 g of KCl, and 90 mg of MXenes, mix and grind to obtain a uniform precursor;
[0041] S2, placing the precursor obtained in step S1 into a porcelain boat and transferring it to a tube furnace, introducing argon gas, heating the precursor to 350°C at a rate of 5°C under an argon atmosphere, maintaining the temperature for 1 hour, and then heating the precursor to 950°C at a rate of 10°C per minute again, maintaining the temperature for 2 hours, performing a melting heating reaction, and cooling the precursor naturally to obtain a product after the reaction;
[0042] S3, adding deionized water to the product obtained in step S2, standing for 24 hours, then ultrasonically treating for 0.5 hours, and drying the obtained product at 60°C;
[0043] S4. Add deionized water to the product dried after ultrasonic treatment in step S3 again for washing, suction filtration, and freeze-drying to finally obtain a tantalum titanium boride / MXenes bimetallic boride heterojunction material.
[0044] 2. Characterization and performance testing:
[0045] The tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared above was characterized and performance tested. Figure 1 This is the SEM image of the Tantalum Titanium Boride / MXenes bimetallic boride heterojunction material; Figure 2 These are the X-ray diffraction spectrum and standard spectrum of tantalum titanium boride / MXenes bimetallic boride heterojunction materials, indicating the successful synthesis of tantalum titanium boride / MXenes bimetallic boride heterojunction materials.
[0046] Tantalum titanium boride / MXenes bimetallic boride heterojunction material is mixed with elemental sulfur to obtain a mixture, in which elemental sulfur accounts for 70% of the mass of the mixture. The mixture is subjected to a vacuum melt diffusion reaction (the reaction temperature is 150°C and the time is 12h) to obtain sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material. Figure 3 The charge and discharge performance of sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material as the positive electrode of lithium-sulfur battery is shown, and the first cycle discharge capacity at 0.1C is 1084mAh g -1 . Figure 4 This is a comparison diagram of the electrochemical impedance spectroscopy (EIS) of the sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared in Example 1 and tantalum titanium boride. It can be seen from the figure that the impedance of the sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material is significantly lower than that of pure tantalum boride, which indicates that the introduction of titanium boride and MXenes can effectively improve the conductivity of the material, reduce the resistance of the material, and improve the electrochemical performance.
[0047] Example 2
[0048] 1. Preparation:
[0049] S1. Weigh 0.13 g of commercial B powder, 0.364 g of Ta2O5, 0.13 g of TiO2, 2.47 g of NaCl, 2.47 g of KCl, and 50 mg of MXenes, mix and grind to obtain a uniform precursor;
[0050] S2, in an argon atmosphere, heating the mixture to 450°C at a rate of 5°C, maintaining the temperature for 1 hour, and then heating the mixture again to 1050°C at a rate of 10°C per minute, maintaining the temperature for 2 hours, performing a melt heating reaction, and cooling the mixture naturally to obtain a product after the reaction;
[0051] S3, adding deionized water to the product obtained in step S2, standing for 24 hours, then ultrasonically treating for 0.5 hours, and drying the obtained product at 60°C;
[0052] S4, adding deionized water to the product dried after ultrasonic treatment in step S3 again for washing, filtering, and freeze-drying to finally obtain a tantalum titanium boride / MXenes bimetallic boride heterojunction material;
[0053] S5. The tantalum titanium boride / MXenes bimetallic boride heterojunction material obtained in S4 is mixed with elemental sulfur to obtain a mixture, wherein the elemental sulfur accounts for 70% of the mass of the mixture, and the mixture is subjected to a vacuum melt diffusion reaction (the reaction temperature is 140° C., and the reaction time is 24 h) to obtain a sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material.
[0054] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a tantalum-titanium boride / MXenes bimetallic boride heterojunction material, characterized in that The steps include: S1. Weigh commercial boron powder, tantalum pentoxide, titanium dioxide, MXenes, sodium chloride and potassium chloride, mix and grind for 30 minutes to obtain a uniform precursor; S2, placing the precursor obtained in step S1 into a porcelain boat, transferring it to a tube furnace, introducing argon gas, heating the temperature to 350-450°C at a rate of 5°C under an argon atmosphere, maintaining it for 1 hour, and then heating it again to 950-1050°C at a rate of 10°C per minute, maintaining it for 2 hours, performing a melting heating reaction, and allowing it to cool naturally to obtain a product after the reaction; S3, adding deionized water to the product obtained in step S2, standing for 24 hours, then ultrasonically treating for 0.5 hours, and drying the obtained product at 60°C; S4. Add deionized water to the product dried after ultrasonic treatment in step S3 again for washing, suction filtration, and freeze-drying to finally obtain a tantalum titanium boride / MXenes bimetallic boride heterojunction material.
2. The method for preparing a tantalum titanium boride / MXenes bimetallic boride heterojunction material according to claim 1, characterized in that: The MXenes described in step S1 is Ti3C2.
3. The method for preparing a tantalum titanium boride / MXenes bimetallic boride heterojunction material according to claim 1, characterized in that: The mass ratio of the total mass of the commercial boron powder, tantalum pentoxide and titanium dioxide described in step S1 to the total mass of sodium chloride and potassium chloride is 1:7-1:
20.
4. The method for preparing a tantalum titanium boride / MXenes bimetallic boride heterojunction material according to claim 1, characterized in that: The molar ratio of tantalum pentoxide, titanium dioxide and commercial boron powder described in step S1 is 1:1:3-1:1:
13.
5. The method for preparing a tantalum titanium boride / MXenes bimetallic boride heterojunction material according to claim 1, characterized in that: The molar ratio of MXenes to commercial boron powder described in step S1 is 1:1-1:
5.
6. A tantalum titanium boride / MXenes bimetallic boride heterojunction material prepared by the preparation method according to any one of claims 1 to 5.
7. Application of the tantalum titanium boride / MXenes bimetallic boride heterojunction material according to claim 6 in the field of lithium-sulfur batteries.
8. The use according to claim 7, characterized in that: During the application process, the tantalum titanium boride / MXenes bimetallic boride heterojunction material is first mixed with elemental sulfur to obtain a mixture, and the mixture is subjected to a vacuum melt diffusion reaction to obtain a sulfur / tantalum titanium boride / MXenes bimetallic boride heterojunction material as a positive electrode material for a lithium-sulfur battery.
9. The use according to claim 7, characterized in that: The temperature of the vacuum melting diffusion reaction is 150-160° C., and the time is 12-24 hours; the elemental sulfur accounts for 75% of the mass of the mixture.
Citation Information
Patent Citations
Lithium-sulfur battery cathode material containing metal borides
CN108963196A
Mercapto-aryl functionalized MXene material and preparation method and application thereof
CN111302992A
Method for preparing refractory metal boride through two steps
CN112250080A
Novel two-dimensional transition metal boride, preparation method thereof and application of novel two-dimensional transition metal boride as energy storage electrode material
CN114956108A
Vanadium boride / vanadium nitride / MXenes heterojunction material and preparation method and application thereof
CN117133875A